The breast reconstruction process of women with breast cancer: A theoretical model O processo de reconstrução mamária da mulher com câncer de mama: Um modelo teórico El proceso de reconstrucción de la mama en mujeres con cáncer de mama: Un modelo teórico - Volkmer C. (2019)
© 2019, Universidade Federal de Santa Catarina. All rights reserved.Objective: to build a theoretical model on the experience and meaning of the breast reconstruction process in women with breast cancer. Method: a qualitative research using Grounded Theory and Symbolic Interactionism as theoreticalmethodological frameworks. Data collection and analysis occurred simultaneously, from April to October 2015, through theoretical sampling and theoretical saturation of the categories. Theoretical sample with 31 participants, 21 women and 10 health professionals, interviewed at home or at work, comprising four sample groups. Results: the theoretical model “Women face challenges and overcome difficulties: fear of death, breast mutilation and breast reconstruction, changing the way of being a woman” offers an explanation of the phenomenon and emerged from the systematic interrelation of the 11 study categories, with three causal categories, one category representing the context, five categories of intervening conditions, the strategies and the consequences represented by one category each. Conclusion: this study demonstrates the experience of the breast reconstruction process for women with breast cancer, the meaning of overcoming difficulties, value life and oneself, putting themselves first, taking care of themselves and learning to change, to be more tolerant, to value material things less and to face life with courage and faith. It also indicates that research on theoretical models on issues that plague our professional practices can enhance teaching and science and, consequently, improve care in women’s health.